Lechoń nieoczywisty - Geraga, Magdalena (Archiwum Emigracji. Studia – Szkice – Dokumenty, 2020)
SURPRISING LECHOŃ Surprising Lechoń was inspired by the reading of unpublished letters of Smosarska, Grydzewski and Czermański to Lechoń, which are stored at the Archives of Emigration in Toruń. What emerges from the study of the letters is a portrait of a terribly interesting man, who was, however, full of contradictions, secrets, and ambiguities. The letters direct us towards other documents (books, articles, recollections, published letters), situating the poet in a new perspective.